Performance evaluation of a HMA pavement longitudinal joint containing a void reducing asphalt membrane (VRAM) - Kamau, Joyce; Podolsky, Joseph; Williams, R. Christopher (Frontiers in Materials, 2023)
Longitudinal joint cracking in Hot Mix Asphalt (HMA) pavements is a major issue that occurs because high density (low air voids) is not easily achieved during construction as compared to the mat away from the joints. High air voids allow water infiltration, which results in moisture-induced damage to the pavement and reduced pavement service life. The use of a Void Reducing Asphalt Membrane (VRAM) has been recommended and used at longitudinal joints of asphalt pavements as a preventative treatment to achieve good performance and increase density/reduce air void content at the longitudinal joint. The Void Reducing Asphalt Membrane material is sprayed on top of a tack coat at the longitudinal joint, 9 inches on each side of the joint below the Hot Mix Asphalt surface overlay, and is expected to migrate upward into the Hot Mix Asphalt overlay, filling 50%–70% of the air voids. This study evaluated and compared the performance of longitudinal joints constructed with Void Reducing Asphalt Membrane to that of a joint without Void Reducing Asphalt Membrane (control). Field cores were collected from 1) a section containing Void Reducing Asphalt Membrane and 2) a section without Void Reducing Asphalt Membrane that was paved for this research. Falling head permeability was carried out to determine the permeability coefficient of the specimen. Disk Compact Tension (DCT) and Semi-Circular Bend (SCB) tests were used to evaluate the cracking performance at low temperatures. A push-pull test was used to evaluate the improvement in adhesion between the top and bottom Hot Mix Asphalt layers at the intermediate temperature. The VRAM-containing samples show high values of fracture energy (Gf) and surface and joint bond energies as compared to the control sections. High surface and joint bond energies indicate that longitudinal cracking at the joints will be delayed as more energy is required to initiate cracks. Additionally, the VRAM-containing samples have a lower permeability coefficient compared to the control section. This indicates that the Void Reducing Asphalt Membrane reduces the possibility of water infiltration. The elastomeric polymer in the Void Reducing Asphalt Membrane increases the cohesion in the mixture, which increases the resistance to deformation and improves the bond strength of the joint Additionally, the Void Reducing Asphalt Membrane enhances the elasticity of the binder, thus increasing the cracking resistance of the joint.